EVALUATION OF EPIDEMIOLOGICAL AND EPIZOOTIOLOGICAL SITUATION ON ANTHRAX IN 2016, THE FORECAST FOR 2017 - A. G. Ryazanova; E. I. Eremenko; L. Y. Aksenova; O. V. Semenova; N. P. Buravtseva; T. M. Golovinskaya; А. N. Kulichenko (Проблемы особо опасных инфекций, 2017)
The results of analysis of epidemiological and epizootiological situation on anthrax in the world in 2016 are presented. In the Russian Federation 36 human cases of anthrax are registered. Epizooties are noted in 3 federal districts. Anthrax in humans was detected in neighboring countries of Central Asia, in a number of Asian and African countries. Epizootic foci are identified throughout with prevalence in the countries of Africa and Asia, where anthrax cases among wild animals were also revealed. The unstable situation on anthrax is forecasted in 2017 in the Russian Federation and neighboring countries.